1992
DOI: 10.4141/cjps92-130
|View full text |Cite
|
Sign up to set email alerts
|

Genotype variation in BOAA, condensed tannins, phenolics and enzyme inhibitors of grass pea (Lathyrus sativus)

Abstract: phenolics and enzyme inhibitors of grass pea (Lttthyrus sativus). Can. J. Plant Sci.72: 1037Sci.72: -1047 Genotypic variability in the neurotoxin, beta-N-oxalyl-amino-L-alanine (BOAA), condensed tannins and phenolics, and protein inhibitors of trypsin, chymotrypsin and alpha-amylase was investigated in 100 lines of Lctthyrus sctivr.rs (grass pea) germplasm maintained at the Morden Research Station. The ranges for these antinutrients (overall means in the parentheses) were as follows: 'SOnnO.UU-;.20(2.g5tg,k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
1
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 3 publications
2
19
1
2
Order By: Relevance
“…As reported by Desphande and Campbell (1992) and Campbell (1997), seed coat color of grass pea is closely associated with the color of flowers. The present research results have confirmed this statement.…”
Section: Discussionsupporting
confidence: 57%
“…As reported by Desphande and Campbell (1992) and Campbell (1997), seed coat color of grass pea is closely associated with the color of flowers. The present research results have confirmed this statement.…”
Section: Discussionsupporting
confidence: 57%
“…In common with many other pulses, the seed protein is relatively rich in lysine (-7 gper 16 g N) but is regarded to be deficient in methionine and tryptophan for nonruminants (Duke et al 1981). Low (1980) derived the following ranges from reports containing proxi- (Roy and Bhat 1975;Deshpande and Campbell 1992) although it is the presence of a neurotoxin that is the major concern in those countries (e.g. Bangladesh, Ethiopia and India) where this crop is an indigenous source of food.…”
mentioning
confidence: 99%
“…Research Centre, Morden, Manitoba (Deshpande and Campbell 1992). Emphasis in the breeding program there has been placed on low-toxin lines while maintaining the favourable agronomic characteristics compared with the pulse crops normally produced in the prairie region.…”
mentioning
confidence: 99%
“…Στα ψυχανθή οι ολιγοσακχαρίτες βρίσκονται σε σημαντικές συγκεντρώσεις ωστόσο η περιεκτικότητά τους διαφέρει ανάμεσα στα είδη (Saini, 1989 Manach et al, 2004;Reed et al, 1995). Σχετίζονται με το χρώμα των σπόρων των οσπρίων και πιο συγκεκριμένα όσο πιο σκούρο είναι το χρώμα τόσο μεγαλύτερη είναι η περιεκτικότητα των οσπρίων σε ταννίνες (Deshpande & Campbell, 1992).…”
Section: ολιγοσακχαρίτεςunclassified
“…Στα ψυχανθή οι ολιγοσακχαρίτες βρίσκονται σε σημαντικές συγκεντρώσεις ωστόσο η περιεκτικότητά τους διαφέρει ανάμεσα στα είδη (Saini, 1989 Manach et al, 2004;Reed et al, 1995). Σχετίζονται με το χρώμα των σπόρων των οσπρίων και πιο συγκεκριμένα όσο πιο σκούρο είναι το χρώμα τόσο μεγαλύτερη είναι η περιεκτικότητα των οσπρίων σε ταννίνες (Deshpande & Campbell, 1992).Κατατάσσονται στους αντιδιατροφικούς παράγοντες των ψυχανθών γιατί μειώνουν τη θρεπτική τους αξία καθώς έχουν την ικανότητα να δημιουργούν σύμπλοκα με τις πρωτεΐνες και εμποδίζουν τη βιοδιαθεσιμότητά τους (Bravo et al, 1993;Chung et al, 1998;Reed et al, 1995;Yoshida et al, 2000). Ακόμη έχει παρατηρηθεί ότι δεσμεύουν χηλικά μέταλλα εμποδίζοντας την απορρόφησή τους (Hill, 2003;Santos-Buelga & Scalbert, 2000).…”
unclassified